Pengaruh Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi Provinsi Riau Tahun 2012-2021 - Khairunnisa Aydiawan Nasution; Nurfahmiyati (UNISBA Press, 2023)
Abstract. The city of Tasikmalaya Economic growth can be measured by looking at the development of Gross Regional Domestic Product at constant prices (real GRDP). Riau Province has the second highest GRDP value on the island of Sumatra, but in 2020 it experienced minus economic growth and Riau Province government spending decreased in 2020 and 2021. This study aims to determine the effect of government spending on economic growth in Riau Province.The analysis technique used in this study is panel data regression analysis with the Random Fixed Model (REM) approach and uses secondary data from the Central Statistics Agency (BPS) in the form of government expenditure data and economic growth in the period 2012-2021. The results of the analysis show that the government expenditure variable has a negative and significant effect on the economic growth of Riau Province. This is because the economic sectors, namely production, distribution, consumption and economic balance affected by government spending are still less than optimal so that government spending has no effect on economic growth in Riau Province. Abstrak. Pertumbuhan ekonomi dapat diukur dengan melihat perkembangan Produk Domestik Regional Bruto atas dasar harga konstan (PDRB riil). Provinsi Riau memiliki nilai PDRB tertinggi kedua di Pulau Sumatera, namun pada tahun 2020 sempat mengalami pertumbuhan ekonomi yang minus dan pengeluaran pemerintah Provinsi Riau mengalami penurunan pada tahun 2020 dan 2021. Penelitian ini bertujuan untuk mengetahui pengaruh pengeluaran pemerintah terhadap pertumbuhan ekonomi di Provinsi Riau. Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi data panel dengan pendekatan Random Fixed Model (REM) dan menggunakan data sekunder yang berasal dari Badan Pusat Statistik (BPS) berupa data pengeluaran pemerintah dan pertumbuhan ekonomi dalam periode tahun 2012-2021. Hasil analisis menunjukkan bahwa variabel pengeluaran pemerintah berpengaruh negatif dan signifikan terhadap pertumbuhan ekonomi Provinsi Riau. Hal ini dikarenakan sektor perekonomian yaitu produksi, distribusi, konsumsi dan keseimbangan perekonomian yang dipengaruhi oleh pengeluaran pemerintah masih kurang optimal sehingga pengeluaran pemerintah tidak berpengaruh terhadap pertumbuhan ekonomi di Provinsi Riau. Kata Kunci: Pengeluaran Pemerintah, Pertumbuhan Ekonomi.